Case Report: Primary Mediastinal Large B-Cell Lymphoma Invasion of Extranodal Thyroid Tissue Mimicking Tuberculosis and Confounded by Similar Ultrasonic Appearance - Wang, Ying; Chen, Menghan; Ni, Chen; Tong, Jiahui; Chen, Peijun; Zhang, Ying; Yang, Gaoyi (Frontiers in Oncology, 2022)
Background: Primary mediastinal large B-cell lymphoma (PMBCL) is a rare type of diffuse large B-cell lymphoma, which has significant features that overlap with those of Hodgkin’s lymphoma. Ultrasound is a common tool in characterizing superficial lymph nodes. In daily medical work,we often need to distinguish lymphoma from lymph node tuberculosis through ultrasonic characteristics. Although lymphoma is common, involvement of extranodal tissue is rare . Case Presentation: Here, we report a 42-year-old Chinese male patient with PMBCL who was misdiagnosed as tuberculosis due to extranodal invasion. He visited the hospital for a neck mass that had been observed for 1 week. Ultrasound revealed multiple enlarged lymph nodes on both sides of the neck. The lesions appeared to involve the surrounding soft tissue and thyroid gland, resembling a tuberculous sinus tract formation. Cervical spine computed tomography showed no obvious abnormalities in the cervical cone or bone damage. A density of patchy fluid was also observed on the posterior wall of the larynx. Contrast-enhanced ultrasound (CEUS) suggested a rich blood supply, showing centripetal enhancement, high enhancement at the peak, and no internal area without enhancement. The patient underwent two ultrasound-guided punctures, with the first puncture performed for an enlarged lymph node in the right neck at Hangzhou Red Cross Hospital. Hodgkin’s lymphoma was considered based on pathological and immunohistochemical findings, whereas aggressive large B-cell lymphoma was considered at Zhejiang Cancer Hospital. Finally, surgical resection was performed under local anesthesia Zhejiang Cancer Hospital, and the pathological results of a frozen section indicated PMBCL. Conclusion: Lymphoma is often misdiagnosed, resulting in delayed initiation of treatment and affecting patient outcomes as the disease progresses. Our case demonstrates that the sonographic appearance of lymphoma may sometimes be confused with tuberculosis. Although ultrasound-guided needle biopsy has a high diagnostic accuracy, it may also cause diagnostic deviation due to insufficient sampling volume. Moreover, due to multiple lymph node enlargements caused by lymphoma or lymph node tuberculosis, punctures of different lymph nodes may present different results.